Sustainability-oriented management in the SMEs: A multilevel analysis in the European Union - Maman, A.; Dias, J. G.; Bassi, F. (Journal of Environmental Management, 2024)
This research focuses on SMEs in the EU and their acceptance of circular economy practices, with a special attention to the structural characteristics that might be significant drivers. Eight indicators of environmentally friendly practices are studied: water saving, energy saving, renewable energy, material saving, waste reduction, sale of waste materials, waste recycling, and eco-designed products. A sample of European SMEs from EU-28 data (countries at the time of the survey) is used to test hypotheses through eight multilevel probit regression models. Company- and country-level covariates are added to the multilevel models. The results showed that the number of employees, the business sector and the type of products/services sold have an impact on environmentally friendly practices. On the other hand, at the national level, per capita GDP and greenhouse gas emissions are the most relevant factors in the eight models. These findings are relevant for the implementation of the European Green Deal, which aims to increase resource efficiency through the transition to a cleaner EU and circular economy.